Total Lesion Glycolysis Estimated by a Radiomics Model From CT Image Alone - Si, Hongwei; Hao, Xinzhong; Zhang, Lianyu; Xu, Xiaokai; Cao, Jianzhong; Wu, Ping; Li, Li; Wu, Zhifang; Zhang, Shengyang; Li, Sijin (Frontiers in Oncology, 2021)
Purpose: In this study, total lesion glycolysis (TLG) on positron emission tomography images was estimated by a trained and validated CT radiomics model, and its prognostic ability was explored among lung cancer (LC) and esophageal cancer patients (EC). Methods: Using the identical features between the combined and thin- section CT, the estimation model of SUVsum (summed standard uptake value) was trained from the lymph nodes (LNs) of LC patients (n= 1239). Besides LNs of LC patients from other centers, the validation cohorts also included LNs and primary tumors of LC/EC from the same center. After calculating TLG (accumulated SUVsum of each individual) based on the model, the prognostic ability of the estimated and measured values were compared and analyzed. Results: In the training cohort, the model of 3 features was trained by the deep learning and linear regression method. It performed well in all validation cohorts (n=5), and a linear regression could correct the bias from different scanners. Additionally, the absolute biases of the model were not significantly affected by the evaluated factors included LN metastasis or not. Between the estimated natural logarithm of TLG (lnTLGe) and the measured values (lnTLGm), significant difference existed among both LC (n=137, bias=0.510±0.519, r=0.956, P=0.000) and EC patients (n=56, bias=0.251± 0.463, r=0.934, P=0.000). However, for both cancers, the overall shapes of the curves of hazard ratio (HR) against elnTLG or mlnTLG were quite alike. Conclusion: Total lesion glycolysis can be estimated by three CT features with particular coefficients for different scanners, and it similar to the measured values in predicting the outcome of cancer patients.